Comprehensive comparison between 222 CTLA-4 haploinsufficiency and 212 LRBA deficiency patients: a systematic review - BARIŞ, SAFA (WILEY, 2021)
Cytotoxic T lymphocyte antigen 4 (CTLA-4) haploinsufficiency (CHAI) and lipopolysaccharide-responsive beige-like anchor (LRBA) deficiency (LATAIE) are newly identified inborn errors of immunity with shared molecular pathomechanisms and clinical manifestations. In this review, we aimed to provide differential comparisons regarding demographic, clinical, immunological and molecular characteristics between these two similar conditions. A literature search was conducted in PubMed, Web of Science and Scopus databases and included studies were systematically evaluated. Overall, 434 (222 CHAI and 212 LATAIE) patients were found in 101 eligible studies. The CHAI patients were mainly reported from North America and western Europe, while LATAIE patients were predominantly from Asian countries. In CHAI, positive familial history (P < 0 center dot 001) and in LATAIE, consanguineous parents (P < 0 center dot 001) were more common. In CHAI patients the rates of granulomas (P < 0 center dot 001), malignancies (P = 0 center dot 001), atopy (P = 0 center dot 001), cutaneous disorders (P < 0 center dot 001) and neurological (P = 0 center dot 002) disorders were higher, while LATAIE patients were more commonly complicated with life-threatening infections (P = 0 center dot 002), pneumonia (P = 0 center dot 006), ear, nose and throat disorders (P < 0 center dot 001), organomegaly (P = 0 center dot 023), autoimmune enteropathy (P = 0 center dot 038) and growth failure (P < 0 center dot 001). Normal lymphocyte subsets and immunoglobulins except low serum levels of CD9(+) B cells (14 center dot 0 versus 38 center dot 4%, P < 0 center dot 001), natural killer (NK) cells (21 versus 41 center dot 1%, P < 0 center dot 001), immunoglobulin (Ig)G (46 center dot 9 versus 41 center dot 1%, P = 0 center dot 291) and IgA (54 center dot 5 versus 44 center dot 7%, P = 0 center dot 076) were found in the majority of CHAI and LATAIE patients, respectively. The most frequent biological immunosuppressive agents prescribed for CHAI and LATAIE patients were rituximab and abatacept, respectively. Further investigations into the best conditioning and treatment regimens pre- and post-transplantation are required to improve the survival rate of transplanted CHAI and LATAIE patients.
Keywords: CHAI; CTLA‐ 4; inborn errors of immunity; LATAIE; LRBA; primary immunodeficiency disease